PENGARUH ORIENTASI PASAR TERHADAP ORIENTASI STRATEGIS ALTERNATIF DAN DAMPAKNYA TERHADAP KINERJA BISNIS PADA PERUSAHAAN-PERUSAHAAN DI KOTA TANGERANG DAN JAKARTA INDONESIA - Johan Doerlaksono (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The purpose of this study was to research the influence of the marketorientation on the alternative strategic orientations and their impact on businessperformance on companies in the city of Tangerang and Jakarta, Indonesia. Alternativestrategic orientations in this study is innovation, learning, entrepreneurial and employeeorientations. This research is associative causal relationship to determine a causalrelationship between the independent variable, market orientation, intermediatevariables, innovation, learning, entrepreneurial and employee orientation, anddependent variable, business performance. This study using the Structural EquationModeling (SEM).The results of the SEM analysis shows effect of market orientation oninnovation, learning, entrepreneurship, employee orientation and direct impact onbusiness performance gives the figure a significant correlation. The effect of learningorientation on business performance gives the figures a moderate correlation. Effect ofemployee orientation on business performance gives the figure a low correlation .Innovation and entrepreneurial orientation influence on the business performance givesthe figure a negative correlation.The researcher recommends that the variables thathave significant correlations can be implemented while the variables that have amoderate, low and negative correlation are recommended for future research to improvethe questionnaire‟s statements and respondent terms of both quality and quantity.Key words: Market, Innovation, Learning, Entrepreneurial, Employee, BusinessPerformance.